Identificación de las condiciones de seguridad y salud y medidas de intervención de los trabajadores de la empresa industria de chocolates rivera S.A.S del departamento del Huila (2020)
Rivera is a municipality that is located at the department of Huila, it is recognized for be home to country house of farming production with a big development, an example of this is the familiar country house constitute as the “Industrias de Chocolates Rivera S.A.S” company, which have seven workers, and is object of this study, whose objective is to identify the security and health conditions, and the intervention measures of that company. As methodology, was use a non-experimental design, basically based in the observation of phenomena, taking as sample the 100% of the employees. The instruments used were a check list and a questionnaire, that were focus on the different types of risks who can face the workers on the daily activities, with the purpose of know the actual security and health conditions in the workers and develop a risk matrix based on the GTC-45. The results of the valuation of the risk were classified mostly in “acceptable with specific control”, but no one “non-acceptable”. Based on these risks, was develop an analysis about the recommendations which will adopt the company in the moment they decide to establish an SST and, in this way, improve the employees conditions, invoking the rules.